2019
DOI: 10.21577/0100-4042.20170453
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento De Metodologias Analíticas Para Determinação De Clorpirifós Em Amostras Aquosas Empregando a Microextração Líquido-Líquido Dispersiva Seguida Por HPLC-Uv

Abstract: Recebido em 15/05/2019; aceito em 27/08/2019; publicado na web em 04/12/2019 DEVELOPMENT OF ANALYTICAL METHODOLOGIES FOR THE DETERMINATION OF CHLORPYRYPHES IN AQUEOUS SAMPLES EMPLOYING THE DISPERSIVE LIQUID MICROEXTRACTION FOLLOWED BY HPLC-UV. The miniaturized extraction techniques use less aggressive methods to the environment, since they generate less waste and spend a minimum of organic solvents, besides having a good selectivity and specificity in the extractions. In this context, liquid-liquid dispersive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the rainy season, the chlorpyrifos pesticide was detected in R1 and R2. This substance is mainly applied to corn, soy and cotton crops, to combat various insect infestations, such as the cotton borer and aphid, cartridge caterpillar and soy caterpillar (Oliveira et al, 2020). Some studies have observed the presence of chlorpyrifos (38.94 µg L -1 ; 1.01 µg L -1 and 2.86 ng L -1 ) in river waters near crops (Oliveira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rainy season, the chlorpyrifos pesticide was detected in R1 and R2. This substance is mainly applied to corn, soy and cotton crops, to combat various insect infestations, such as the cotton borer and aphid, cartridge caterpillar and soy caterpillar (Oliveira et al, 2020). Some studies have observed the presence of chlorpyrifos (38.94 µg L -1 ; 1.01 µg L -1 and 2.86 ng L -1 ) in river waters near crops (Oliveira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This substance is mainly applied to corn, soy and cotton crops, to combat various insect infestations, such as the cotton borer and aphid, cartridge caterpillar and soy caterpillar (Oliveira et al, 2020). Some studies have observed the presence of chlorpyrifos (38.94 µg L -1 ; 1.01 µg L -1 and 2.86 ng L -1 ) in river waters near crops (Oliveira et al, 2020). In Brazil, chlorpyriphos was already found in São Paulo, Mato Grosso, Rio Grande do Sul and Sergipe states (Albuquerque et al, 2016).…”
Section: Discussionmentioning
confidence: 99%